Implementasi Inovasi Sekunder dan Penguatan Kapasitas Produksi Kopi Robusta melalui Transfer Teknologi dan Hibah Alat di Desa Gunungjaya, Salem, Brebes - Sugeng Rianto; Sutarmin Sutarmin; Undri Rastuti; Mia Anjani; Tria Putri Yani; Meri Aguk Setiani; M. Hari Ramadhan (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
Salem District is one of the largest coffee commodities in Brebes Regency. This significant potential has yet to provide a meaningful contribution to the income of coffee farmers, especially in Gunung Jaya village, Salem District. The low income of coffee farmers is due to the fact that they still sell their coffee products in the form of cherry. Over time, in 2018, farmers began to develop small-scale and simple coffee processing from green beans to roasted beans and coffee powder, pioneered by the SME "Lulumpang Kopi". They still use simple tools and often have to travel out of town to obtain the desired coffee powder. Lulumpang Kopi can produce 100-150 packages of coffee weighing 100 grams. Seeing this potential, the Community Partnership Empowerment team (PKM) from the University of Civilisation and UNSOED, funded by DIKTISAINTEK, is conducting community service this year 2025 using training methods, workshops, and appropriate technology grants. Thus, technology has been granted in the form of 1 Huller machine with a capacity of 150kg/batch, 1 BBM Grinding machine with a capacity of 10kg/batch, and scales. This assistance aims to enhance farmers' capabilities to achieve greater economic independence and improve their competitiveness in the market. As a result of this activity, partners were able to increase the capacity and quality of coffee farmers' production through the grant of equipment such as huller, BBM grinder, and digital scales, making the processing faster, more efficient, and yielding better coffee compared to traditional methods. In addition, the training participants also demonstrated an increase in knowledge through pre-tests and post-tests, rising from 66.5% to 77.3%, an increase of 13.8% from the 40 participants who attended.